2009
DOI: 10.1016/j.physd.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cardiac tissue anisotropy on re-entrant activation in computational models of ventricular fibrillation

Abstract: Published paper Clayton, R.H (2009) Influence of cardiac tissue anisotropy on re-entrant activation in computational models of ventricular fibrillation. Physica D-Nonlinear Phenomena, AbstractThe aim of this study was to establish the role played by anisotropic diffusion in (i) the number of filaments and epicardial phase singularities that sustain ventricular fibrillation in the heart, (ii) the lifetimes of filaments and phase singularities, and (iii) the creation and annihilation dynamics of filaments and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…22 The anatomically detailed model of rabbit ventricles was based on the dataset developed at the University of California-San Diego, 34 fitted to a regular Cartesian grid with a spacing of 0.25 mm. The cube geometry had dimensions of 50ϫ 50ϫ 50 mm 3 ͑7 762 392 grid points͒; the isotropic and anisotropic slabs had dimensions of 75.0ϫ 75.0 ϫ 17.5 mm 3 ͑6 038 672 grid points͒ and 79.5ϫ 79.5 ϫ 13 mm 3 ͑4 992 800 grid points͒, respectively.…”
Section: B Tissue Geometriesmentioning
confidence: 99%
See 2 more Smart Citations
“…22 The anatomically detailed model of rabbit ventricles was based on the dataset developed at the University of California-San Diego, 34 fitted to a regular Cartesian grid with a spacing of 0.25 mm. The cube geometry had dimensions of 50ϫ 50ϫ 50 mm 3 ͑7 762 392 grid points͒; the isotropic and anisotropic slabs had dimensions of 75.0ϫ 75.0 ϫ 17.5 mm 3 ͑6 038 672 grid points͒ and 79.5ϫ 79.5 ϫ 13 mm 3 ͑4 992 800 grid points͒, respectively.…”
Section: B Tissue Geometriesmentioning
confidence: 99%
“…16,17 Filaments with "positive tension" contract, whereas filaments with "negative tension" extend. 6 Filament dynamics have been documented in a number of computational studies, which have shown that for normal excitability and steep restitution, filaments tend to be short lived, 21,22 and that most filament creation arises from filament division rather than filament birth. 18 Negative filament tension is associated with reduced excitability, which in car-diac tissue mirrors some of the changes seen in myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 type II NLE is estimated from the relation in Eq. (10). The other parameters are determined using Eq.(6).…”
Section: B Stochastic Model Of Phase Singularitiesmentioning
confidence: 99%
“…During VF, many phase singularities (PSs) appear and, therefore, features such as lifetime, total number, and space-time trajectory of them may give new insights into VF. 10 In defect-mediated turbulence, the statistical properties of topological defects (phase singularities) have been studied to reveal the complex nature of the turbulence. [11][12][13][14][15] Gil et al 11 investigated creation and annihilation mechanisms of defect pairs and predicted the probability distribution function of the number of defect pairs in oscillatory media.…”
Section: Introductionmentioning
confidence: 99%